Significant association between HLA‐B*35:01 and onset of drug‐induced liver injury caused by Kampo medicines in Japanese patients. Issue 5 (14th January 2023) - Nakamura, Ryosuke; Arakawa, Noriaki; Tanaka, Yoichi; Uchiyama, Nahoko; Sekine, Akihiro; Mashimo, Yoichi; Tsuji, Keiji; Kagawa, Tatehiro; Sato, Ken; Watanabe, Masaaki; Aiso, Mitsuhiko; Hiasa, Yoichi; et al.
Abstract: Aim: Drug‐induced liver injury (DILI) is a severe and life‐threatening immune‐mediated adverse effect, occurring rarely among treated patients. We examined genomic biomarkers in the Japanese population that predict the onset of DILI after using a certain class of drugs, such as Kampo products (Japanese traditional medicines). Methods: A total of 287 patients diagnosed as DILI by hepatology specialists were recruited after written informed consent was obtained. A genome‐wide association analysis and human leukocyte antigen (HLA) typing in four digits were performed. Results: We found a significant association ( p = 9.41 × 10 −10 ) of rs146644517 ( G > A ) with Kampo product–related DILI. As this polymorphism is located in the HLA region, we evaluated the association of HLA types and found that 12 (63.2%) of 19 Kampo‐DILI patients contained HLA‐B*35:01, whereas only 15.2% were positive for this HLA among healthy volunteers. The odds ratio was 9.56 (95% confidence interval 3.75–24.46; p = 2.98 × 10 −6, corrected p = 4.17 × 10 −5 ), and it increased to 13.55 compared with the DILI patients not exposed to Kampo products. The individual crude drug components in the Kampo products, including Scutellaria root ( ougon in Japanese), rhubarb ( daiou ), Gardenia fruit ( sanshishi ), and Glycyrrhiza ( kanzou ), were significantly associated with HLA‐B*35:01 . Conclusions: HLA‐B*35:01 is a genetic risk factor and a potential predictive biomarker for Kampo‐induced DILI in the Japanese population.